Bullying Di Sekolah: Upaya Pencegahannya Melalui Pendidikan Karakter KH. Ahmad Dahlan - M Shufiadin; Akfi Yusria Rizqi; Moh Sholihuddin (Yayasan Salam Cerdas Al-Fattah, 2025)
This study examines the relevance of K.H. Ahmad Dahlan’s educational thought in developing character education as a strategy to prevent bullying in schools, both in direct physical interactions and within digital spaces that increasingly serve as arenas for symbolic violence. Employing a literature review with descriptive analysis, this research investigates primary sources on Dahlan’s ideas alongside contemporary studies on bullying phenomena, students’ psychosocial dynamics, and character-based pedagogical approaches. The findings indicate that Dahlan’s educational philosophy offers a comprehensive framework: the integration of religious knowledge and modern science strengthens students’ holistic worldview; moral cultivation serves as an ethical foundation that fosters moral sensitivity; teacher exemplarity plays a central role in shaping a humanistic school climate; and well-designed social engagement activities nurture empathy while reducing tendencies to demean others. Moreover, Dahlan’s emphasis on ethical media literacy becomes increasingly relevant in the digital era, where cyberbullying represents a form of violence that is difficult to detect yet has profound psychological impacts on students. Overall, this study affirms that the corpus of K.H. Ahmad Dahlan’s educational thought provides not only normative principles but also practical guidance that can be operationalized as a comprehensive preventive strategy to reduce bullying and to cultivate students’ character, empathy, and capacity to build dignified social relationships.